Study of the proviral load levels and mRNA expression of cytokines in peripheral blood mononuclear cells and somatic milk cells in cattle with different BLV infection profiles - Ladera Gomez, Marla Eliana (2023)
The retrovirus bovine leukemia virus (BLV) might produce abnormal immune function, associated with susceptibility to developing other infectious diseases, including mastitis. This study aimed to determine the proviral load and cytokines gene expression in peripheral blood mononuclear cells (PMBC) and milk somatic cells (SC) in BLV-infected and non-infected cattle. Of 27 BLV-infected cows in PBMC, 17 (62.96%) had a high proviral load (HPL), and 10 (37.04%) had a low proviral load (LPL). All SC samples had low proviral load (LPL-SC). Higher IFN-γ and IL-10 expression, and lower IL-12 and IL-6 expression, were found in PBMC from BLV-infected compared to BLV non-infected cattle. Moreover, higher IFN-γ, IL-12, and IL-6 expression, and lower IL-10 expression were observed in cattle with LPL-PBMC compared to HPL-PBMC. In milk samples, lower IFN-γ and higher IL-12 mRNA expression were observed in LPL-SC compared to BLV non-infected cattle in SC. IL-10 and IL-6 expression mRNA was significantly lower in LPL-SC than in SC from BLV non-infected cattle. This study shows that milk SC maintains lower proviral load levels than PBMC. This first report on Th1 and Th2 cytokines expression levels in SC may be relevant to future control strategies for BLV infection, mastitis, and udder health management.